1994
DOI: 10.3109/02841869409098421
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Results of Neutron Therapy Trials

Abstract: Twenty-five randomised clinical trials have been completed which have investigated the value of fast neutron therapy. The results of these trials are reviewed in terms of the reported rates of local tumour control and late morbidity. The trials have included patients with cancers of the head and neck region, brain, lung, pancreas, cervix, bladder and rectum. None has demonstrated neutrons to be advantageous compared with photons. Two trials of locally advanced prostate cancer have given conflicting results. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Nordsmark et al reported the relationship between tumor hypoxia and poorer tumor response to radiation therapy in patients with head and neck cancers (9). As for carcinoma of the cervix, there are some reports about the relationship between pretreatment intratumoral pO 2 and prognosis (24 -26). Hockel et al reported that pretreatment intratumoral pO 2 of uterine cervical cancer is an important prognostic factor not only for radiation therapy but also for surgical treatment (25).…”
Section: Discussionmentioning
confidence: 99%
“…Nordsmark et al reported the relationship between tumor hypoxia and poorer tumor response to radiation therapy in patients with head and neck cancers (9). As for carcinoma of the cervix, there are some reports about the relationship between pretreatment intratumoral pO 2 and prognosis (24 -26). Hockel et al reported that pretreatment intratumoral pO 2 of uterine cervical cancer is an important prognostic factor not only for radiation therapy but also for surgical treatment (25).…”
Section: Discussionmentioning
confidence: 99%
“…Harold Gray thought that neutrons were a good tool for investigating high-LET effects, but did not think them appropriate for radiotherapy [Dr OCA Scott, London, UK, 2002, personal communication]. Neutrons proved to be disappointing in randomised clinical trials, for reasons that are now better understood [1,7]. It is important that the wealth of experimental data sets produced by British scientists should be analysed as completely as possible and with special attention to any general principles that might guide future research in charged particle therapy.…”
Section: Discussionmentioning
confidence: 99%
“…After the initial enthusiasm following the first reports of their clinical efficiency, FN irradiations have failed to make inroads in current medical practice (Caterall and Errington 1987;Duncan 1994;Laramore and Griffin 1995). Multicentric trials were performed in the 1980's at the initiative of the National Institute of Health, but no clear demonstrations of clinical benefit was made for most cancer types.…”
Section: Discussionmentioning
confidence: 99%